MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM KONTEMPORER: TANTANGAN DAN IMPLEMENTASI : MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM KONTEMPORER: TANTANGAN DAN IMPLEMENTASI - Endi Suhendi; Akbar Agung Gumelar; Neng Astrilestari Putri (STKIP Subang, 2026)
This study addresses the critical issue of rising radicalism, intolerance, and social conflicts that often misuse religious pretexts, presenting a direct challenge to contemporary Islamic education. The primary objective of this research is to explain the definition of religious moderation, analyze the core concepts of Islamic education, and evaluate the implementation of religious moderation within Islamic educational frameworks. To achieve this, a qualitative library research method was employed, utilizing a descriptive-analytic approach to critically evaluate primary and secondary sources. These sources include official documents from the Ministry of Religious Affairs of the Republic of Indonesia and foundational literatures on Islamic education. The data were subsequently analyzed through qualitative analysis techniques, including data reduction, data display, and conclusion drawing. The results obtained indicate that the implementation of religious moderation within Islamic education is successfully carried out by integrating key values such as justice (al-’adl), balance (tawazun), and tolerance (tasamuh) into Islamic Education (PAI) subjects. This integration is supported by participatory learning methods—such as discussions, question-and-answer sessions, and project-based learning—alongside an inclusive school culture and exemplary teacher behavior. Despite positive outcomes in strengthening student character, challenges remain, such as the spread of radical ideologies via social media and limited religious literacy. Ultimately, these findings provide valuable insights into addressing these barriers through enhanced digital literacy, improved teacher competencies, and cross-sectoral collaboration to foster an inclusive, tolerant, and nationalistic generation.